Pemberdayaan Usaha Kecil dan Mikro: Kendala yang Dihadapi dan Solusinya - Rusmiati Rusmiati; Alya Putri Aiska; Dwi Citra Haryati; Thamara Idil Fitri Marliana (Anggaran : Jurnal Publikasi Ekonomi dan Akuntansi, 2025)
Small and Medium Enterprises (SMEs) have an important task in supporting national economic growth, creating jobs and supporting income redistribution. However, SMEs still experience various obstacles that can disrupt their competitiveness and development. This research aims to analyze and identify the main obstacles experienced by SMEs. The research method used in this research is descriptive qualitative. The research results stated that the obstacles experienced in optimizing the development scheme were time and motivation. Apart from thet, the entrepreneur is willing to put into practice what he has learned from training or mentoring in business management.